Ammonia losses and nitrogen partitioning at a southern High Plains open lot dairy. (June 2015) - Todd, Richard W.; Cole, N. Andy; Hagevoort, G. Robert; Casey, Kenneth D.; Auvermann, Brent W.
Abstract: Animal agriculture is a significant source of ammonia (NH3 ). Cattle excrete most ingested nitrogen (N); most urinary N is converted to NH3, volatilized and lost to the atmosphere. Open lot dairies on the southern High Plains are a growing industry and face environmental challenges as well as reporting requirements for NH3 emissions. We quantified NH3 emissions from the open lot and wastewater lagoons of a commercial New Mexico dairy during a nine-day summer campaign. The 3500-cow dairy consisted of open lot, manure-surfaced corrals (22.5 ha area). Lactating cows comprised 80% of the herd. A flush system using recycled wastewater intermittently removed manure from feeding alleys to three lagoons (1.8 ha area). Open path lasers measured atmospheric NH3 concentration, sonic anemometers characterized turbulence, and inverse dispersion analysis was used to quantify emissions. Ammonia fluxes (15-min) averaged 56 and 37 μg m −2  s −1 at the open lot and lagoons, respectively. Ammonia emission rate averaged 1061 kg d −1 at the open lot and 59 kg d −1 at the lagoons; 95% of NH3 was emitted from the open lot. The per capita emission rate of NH3 was 304 g cow −1  d −1 from the open lot (41% of N intake) and 17 g cow −1  d −1 from lagoons (2% of N intake). Daily N input at the dairy was 2139 kg d −1, with 43, 36, 19 and 2% of the N partitioned to NH3 emission, manure/lagoons, milk, and cows, respectively. Highlights: Quantified ammonia emissions at an open lot dairy during summer in New Mexico. Almost half of the nitrogen fed to cows was lost to the atmosphere as ammonia. Almost all ammonia emissions came from the open lot area where cows were housed. Manure handling and animal housing affect the source and magnitude of ammonia loss.